PENYELESAIAN KREDIT MACET DALAM KREDIT PEMILIKAN RUMAH YANG DIBEBANI HAK TANGGUNGAN YANG DI EKSEKUSI DI BAWAH TANGAN (STUDI KASUS BANK RAKYAT INDONESIA CABANG PUTRI HIJAU MEDAN) - ZAKI ALYAMANI (PREMISE LAW JURNAL, 2017)
DOSEN PEMBIMBING:1. Tan Kamello2. Sunarmi3. Suprayitno Credit is a lending and borrowing agreement. Default is a condition in which a debtor fails to pay off all of his debt on the due date. The cause of debtor’s default condition needs to be found early so that it can be prevented or the bank can estimate what factors causing the default and how the bad credits are solved in PT. Bank Rakyat Indonesia, Putri Hijau Branch Office, Medan. The research problem is How the Credit Agreement of House Ownership is implemented in Bank BRI, Putri Hijau Branch Office, Medan? Are there any factors causing the bad credit to the House Ownership in Bank BRI, Putri Hijau Branch Office, Medan? What is the solution to the bad credit to the House Ownership used as mortgage which is executed underhanded by PT BRI, Putri Hijau Branch Office, Medan?Keywords: Bad Credit, Bank Rakyat Indonesia, Bad Credit Settlement, Mortgage Right, Underhanded Execution